Basins of Convergence in a Multi-Perturbed CR3BP - Alicia Herrero; Santiago Moll-Lopez; José-A. Moraño; Erika Vega-Fleitas; Daniel Villalibre (Applied Sciences)
The circular restricted three-body problem (CR3BP) is analyzed to introduce additional factors into the dynamic model, such as radiation forces, flattening of the primary bodies, relativity effects, and the presence of natural satellites. The introduction of these factors increases the accuracy when obtaining the position of the Lagrange points and the basins of convergence of the system. The Newton–Raphson methodis used to implement a searching algorithm. Finally, an application to the Sun–Mars system including the presence of Phobos and Deimos is developed.